1995
DOI: 10.1121/1.411994
|View full text |Cite
|
Sign up to set email alerts
|

On the use of variable order infinite wave envelope elements for acoustic radiation and scattering

Abstract: The use of the variable order infinite wave envelope element to model acoustic radiation and scattering problems is investigated. Different acoustic modeling aspects are focused upon. These involve the modeling of acoustic wave propagation above infinite homogeneous impedance planes, different methods to prescribe acoustic sources and alternative postprocessing procedures. Special attention is given to limitations encountered for this finite element based modeling of wave propagation in unbounded domains. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…The condition number κ(A) is given by the ratio of the largest to the lowest eigenvalue of the frequency-dependent matrix A and is calculated by power iteration and inverse iteration, respectively. As shown by Babuška et al 41 Cremers et al 42 and Dreyer et al 6 the matrix condition increases with the polynomial order, which leads to ill-conditioned matrices for polynomials of degree > 8 in the case of Lagrange polynomials, whereas Legendre and Jacobi polynomials provide distinctly better-conditioned matrices. Tests performed by the authors of this paper have confirmed this observation, although the choice between the four polynomials had no considerable effect on the modes in exterior acoustics, as will be shown subsequently.…”
Section: Matrix Condition Numbermentioning
confidence: 98%
“…The condition number κ(A) is given by the ratio of the largest to the lowest eigenvalue of the frequency-dependent matrix A and is calculated by power iteration and inverse iteration, respectively. As shown by Babuška et al 41 Cremers et al 42 and Dreyer et al 6 the matrix condition increases with the polynomial order, which leads to ill-conditioned matrices for polynomials of degree > 8 in the case of Lagrange polynomials, whereas Legendre and Jacobi polynomials provide distinctly better-conditioned matrices. Tests performed by the authors of this paper have confirmed this observation, although the choice between the four polynomials had no considerable effect on the modes in exterior acoustics, as will be shown subsequently.…”
Section: Matrix Condition Numbermentioning
confidence: 98%
“…The main conclusion of this paper is that the special wave ÿnite elements can be combined with classical wave inÿnite elements to achieve solutions to wave problems of high accuracy. It can be conjectured that the special wave ÿnite elements could also be combined with other, more recent wave inÿnite elements which have more general mappings, due to Astley [5], Cremers et al [6,8], Burnett and Holford [9] and others. It would be necessary, of course, to match the directions of wave propagation at the special wave ÿnite element=inÿnite element interface.…”
Section: Resultsmentioning
confidence: 97%
“…The extension of the mapping so as to allow inÿnite elements to have arbitrary pole locations so that they can be placed on arbitrary boundary was applied to wave envelope elements using conjugate weighting functions by Astley [5] and Cremers et al [6], and to the quadratic unconjugated wave inÿnite element by Bettess and Bettess [7]. Cremers and Fyfe [8] developed wave envelope elements using linear or quadratic mapping in the angular direction and a variable order of inÿnite mapping in the radial direction for three dimensional problems. More modern ellipsoidal inÿnite elements have been developed by Burnett and Holford [9] and others.…”
Section: Introductionmentioning
confidence: 99%
“…For high radial orders, though, the early concepts of Astley-Leis elements led to extremely ill-conditioned system matrices [26]. Therefore, it was recommended to avoid both high radial polynomial orders as well as envelopes close to the radiating body [25]. Despite this deÿciency the Astley-Leis elements perform well and are already introduced in professional software packages [33].…”
Section: Stability and Ill-conditioningmentioning
confidence: 99%